Potential improvement of biogas production from fallen teak leaves with co-digestion of microalgae - Anongnart Wannapokin (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Biogas production from anaerobic co-digestion of fallen teak leaves (Tectona grandis) and microalgae (Chlorella vulgaris) were investigated. In this study, teak leaves and algae mixtures with or without pretreatment were used as the substrates and digested in 1-L of anaerobic fermenter, then optimal conditions were performed in 6-L fermenter. Pretreatment was performed using sodium hydroxide (NaOH) solution (w/v) at different conditions (0, 2, 3 and 4%), with different total solid (TS) ratios (10, 15 and 20%). The digesters were placed in an incubator at 34–36 °C for 45 days. The results showed that the co-digestion of pretreated (10% TS with 2% NaOH) of teak leaves and algae was significantly higher in terms of biodegradability of TS, VS, COD along with biogas yield, methane potential and highest yield was achieved 71.90% than those obtained by mono-digestion. Thus, results demonstrated that anaerobic fermentation of teak leaves and microalgae in digester system could get as high methane yield.